A longitudinal study of growth and relation with anemia and iron overload in pediatric patients with transfusion-dependent thalassemia - Kwannapas Nokeaingtong (2018)
Copyright © 2016 Wolters Kluwer Health, Inc. All rights reserved. Short stature is one of the most common endocrinopathies in transfusion-dependent thalassemia (TDT). This study aimed to determine the longitudinal pattern of growth in pediatric patients with TDT and study the relationship between growth and hemoglobin level, serum ferritin level/iron overload parameters, and other clinical factors. The interval height-for-age Z-scores (HAZ) of 50 patients with TDT, of a mean age of 13.3±2.8 years, were analyzed using linear mixed model analysis. Nineteen patients (38%) had short stature with HAZ ≤-2.0. The prevalence of short stature increased with age. The estimated mean HAZ decreased by 0.19SD per year from the age of 5 years until approximately 14 years (95% confidence interval [CI],-0.22 to-0.16, P<0.001). Male sex (estimate,-0.28; 95% CI,-0.43 to-0.14; P<0.001), mean 3-year hemoglobin level ≤8 g/dL (estimate,-0.36; 95% CI,-0.53 to-0.19; P<0.001), mean 3-year ferritin level ≥ 1800 ng/mL (estimate,-0.44; 95% CI,-0.59 to-0.29; P<0.001), and cardiac T2∗≤20 ms (estimate,-1.05; 95% CI,-1.34 to-0.77; P<0.001) were significantly associated with short stature. In conclusion, short stature in patients with TDT is common and relates significantly with increasing age, male sex, hemoglobin level, and iron overload status.